LEVEL OF PERCEIVED BEHAVIOURAL CONTROL AND ITS IMPACT ON JAWI ACCEPTANCE AMONG INDIANS COMMUNITY IN MALAYSIA: Mohd Khairull bin Ab Ghani - Khairull, Mohd (Qawwam : The Leader's Writing, 2022)
The issue of introducing the teaching of Jawi script or khat calligraphy in schools has become a serious issue, as it is facing intense opposition by the non-Malay-Muslims. The issue of introducing a six-page lesson on khat calligraphy in the Year 4 Bahasa Malaysia textbook for vernacular schools also has bring about some hot reactions by political leaders, educationists, and community groups. This is due to the misconception towards the word Jawi itself as most who are against it thought that it is an Islamic teaching when it is actually just a form of Arabic writing system. Therefore, this study aims to identify the role of perceived behavioural control in explaining the acceptance of Indian community in Malaysia towards Jawi-Khat. This study was conducted in Malaysia with a total of 192 respondents. The sampling technique used is convenient sampling. The findings of the study has proven that perceived behavioural control is positive and significant towards the acceptance of Jawi among the Indians community in Malaysia.